Diversity and Elevational Levels of Lichens in Western Tianshan National Nature Reserve in Xinjiang, China - Anwar Tumur; Reyim Mamut; Mark R. D. Seaward (Diversity)
Western Tianshan National Nature Reserve in Xinjiang, China stands out for its uniqueness and high biodiversity, including lichens. This study aims to characterize lichen diversity and compare distribution patterns of different life forms, substratum affinities and photobiont types. Surveys were conducted from June to August 2024 using stratified sampling methods at elevation ranging from 1100 m to 3400 m in the study area. Morphological, anatomical and chemical studies revealed 173 lichen species from 24 families and 58 genera, of which 100 species were identified as crustose, 46 as foliose and 27 as fruticose. Among the different habitat groups, strictly saxicolous lichens were dominant with 89 species, followed by corticolous lichens with 44 species and terricolous lichens with 40 species. The total species richness of lichens has a bimodal pattern: one peak appears at a low altitude (1701–2000 m) and the other at a high altitude (2901–3200 m). Among the three substratum categories studied, the species richness of terricolous lichens showed a unimodal relationship with elevation, and the saxicolous lichen had a bimodal pattern. The species richness of corticolous lichens was highest at lower and medium elevations and decreased at higher elevations. With respect to photobiont type, the species richness of cyanolichens showed a unimodal relationship with elevation. Maximum richness occurred at 2700 m, contrary to the chlorolichens, which had a bimodal pattern. Species richness of all three growth forms of lichens showed a bimodal pattern related to elevation. Among the three morphological types, crustose and foliose species richness had their highest values of 38 and 19, respectively, at 1701–2000 m, and fruticose lichens peaked with a maximum of 13 species at 2301–2600 m. The species richness of crustose lichens is lowest between altitudes 2300 and 2600 m, while the lowest species richness of fruticose and foliose lichens occurs at 2001–2300 m and elevations above 2900 m.